Characterization of primaquine imidazolidin-4-ones with antimalarial activity by electrospray ionization-ion trap mass spectrometry - Nuno Vale (2008)
The extensive characterization by electrospray ionization-ion trap mass spectrometry (ESI-MS(n)) of 20 imidazolidin-4-ones derived from the antimalarial primaquine was well obtained. These compounds are being under investigation as potential antimalarials, as they have been previously found to be active against rodent P. berghei malaria and to be highly stable under physiological conditions. Experiments by collision-induced dissociation (CID) in the nozzle-skimmer region or by tandem-MS have shown the title compounds to be remarkably stable. Mechanisms are proposed to explain the major fragmentations observed in ESI-MS(n) experiments. Overall, this work represents an unprecedented contribution to a deeper insight into imidazolidin-4-one antimalarials based on a classic 8-aminoquinolinic scaffold. Data herein reported and discussed may be an useful guide for future studies on therapeutically relevant molecules possessing either the 8-aminoquinoline or the imidazolidin-4-one motifs.